Editorial: Healthcare cost and financing - Abdul Rani, Mohammed Fauzi (Faculty of Medicine, International Islamic University Malaysia, 2010)
There are two types of healthcare systems in Malaysia, the public and the private. Each contributes differently depending on the assessment criteria. In 2009 for example, there were 3 admissions in the public healthcare institutions for a single hospital admission in the private sector. The comparison for outpatient clinic appointments is even more dramatic, the ratio of 6 to 1, overwhelmingly in favour of public healthcare institutions. Translating these fi gures to costs refl ects somewhat altered proportions to the service ratios that we have seen. In 2008, the total healthcare expenditures for both public and private sectors was around RM35 billion, RM18.8 billion from the public and RM 16.2 billion privately, or approximately 53.8% to 46.2% respectively, an almost parity1....